Training Strategies Affecting Performance Efficiency among Operation Officers in Bank for Agriculture and Agricultural Cooperatives, Roi Et Province - ปัญโยวัฒน์, ดุจเดือน; พรหมราษฎร์, ภัทริยา (Journal of Roi Et Rajabhat University, 2019)
This research aims to 1) study training strategies and performance efficiency of operation officers of Bank for Agriculture and Agricultural Cooperatives Roi Et Province, 2) compare the performance efficiency of operation officers classified by personal data and 3) study the effects of training strategies on the performance efficiency of the operation officers. The data were collected by using questionnaires from 360 samples. The data were analyzed by descriptive statistics, independent t-test, one way ANOVA, correlation coefficients and multiple regression analyses. The result found that the training strategies of Bank for Agriculture and Agricultural Cooperatives, Roi Et Province was high level. The performance efficiency of operation officers was high level. The comparison of performance efficiency of operation officers classified by personal data found that the term of gender, educational level and position were not different in performance efficiency. In contrast, age and experience were different in performance efficiency. Training strategies and performance efficiency had positive relation at high level. Three aspects of training strategies; knowledge sharing, learning by operation officers’ needs and the partnership of educational institutions, affected the performance efficiency. The most affecting to performance efficiency was knowledge sharing.